Evaluasi Program Diniyah Di Mts Al Muddatsiriyah Jakarta Pusat - Naniek Nurdiani (CV. Kayaswara, 2025)
One element of education that can then serve as a benchmark for the development and effectiveness of a program is evaluation. It can be said that this is still being implemented, especially in the Diniyah Program at MTS Al Muddatsiriyah Central Jakarta, so it still needs improvement and refinement in its implementation. In this study combined with descriptive methods with a qualitative approach. The evaluation model used is CIPP (Context, Input, Process, and Product). The object of this study is MTS Al Muddatsiriyah Central Jakarta. The results of the study stated that the results of the evaluation of the diniyah program at MTS Al Muddatsiriyah Central Jakarta: 1) In terms of Context, the Diniyah program at MTS Al Muddatsiriyah Central Jakarta obtained a percentage of 75% in the good category with details of the background, vision and mission of the program, program objectives, the drawback is the absence of the Diniyah Program Decree, 2) In terms of input, this diniyah program obtained a 100% percentage with a very good category due to testing at the time of admission of new students, program teaching staff in accordance with their expertise, and the existence of facilities and infrastructure that support the running of the diniyah program, 3) In terms of Process, the diniyah program at MTS Al Muddatsiriyah obtained a percentage of 100% with a very good category because the learning process has been running well, 4) In terms of Product, this diniyah program obtained a percentage of 100% because the majority of students at MTS Al Muddatsiriyah have memorized habituation readings, are able to write Arabic and Malay Arabic, are able to read the Qur'an well, and have better character and personality.